2017
DOI: 10.1186/s13073-017-0486-1
|View full text |Cite|
|
Sign up to set email alerts
|

Linkage, whole genome sequence, and biological data implicate variants in RAB10 in Alzheimer’s disease resilience

Abstract: BackgroundWhile age and the APOE ε4 allele are major risk factors for Alzheimer’s disease (AD), a small percentage of individuals with these risk factors exhibit AD resilience by living well beyond 75 years of age without any clinical symptoms of cognitive decline.MethodsWe used over 200 “AD resilient” individuals and an innovative, pedigree-based approach to identify genetic variants that segregate with AD resilience. First, we performed linkage analyses in pedigrees with resilient individuals and a statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
66
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 59 publications
7
66
0
1
Order By: Relevance
“…The Rab10 gene is linked to human disease in several ways. Genetic variants in Rab10 associate with resilience to AD, and a phosphorylation site in the Rab10 switch II domain is upregulated by PD-associated mutations in the LRRK2 protein kinase 11 . LRRK2-mediated phosphorylation of Rab10 is strongly affected by all known pathogenic mutations as well as PD-risk factor genetic variants like G2385R, with Rab10 phosphorylation changing the affinity of different binding proteins to the Rab10 effector loops 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The Rab10 gene is linked to human disease in several ways. Genetic variants in Rab10 associate with resilience to AD, and a phosphorylation site in the Rab10 switch II domain is upregulated by PD-associated mutations in the LRRK2 protein kinase 11 . LRRK2-mediated phosphorylation of Rab10 is strongly affected by all known pathogenic mutations as well as PD-risk factor genetic variants like G2385R, with Rab10 phosphorylation changing the affinity of different binding proteins to the Rab10 effector loops 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Further, a rare variant of the Rab10 gene has been shown to confer resilience for AD development in people over the age of 75 who carry at least one APOE ε 4 allele. This, together with the reported increased expression of Rab10 mRNA in the temporal cortex of AD brains [6] and the in vitro studies showing overexpression of Rab10 increases Aβ production in cultured neuroblastoma cells [6], provide compelling evidence for an important role of Rab10 in AD.…”
Section: Discussionmentioning
confidence: 86%
“…Interestingly, a recent study has identified a rare variant of the Rab10 gene in cognitively normal individuals over the age of 75 who carry at least one APOE ε 4 allele, a known AD genetic risk factor [6], suggesting the Rab10 genetic variation may be protective against AD development.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations